Pyrolysis behavior and mechanism of high nitrogen compound 4,4′,6,6′-tetra(azido)-hydrazine-1,3,5-triazine - Rui-min Tang; Chen Wang; Mao-guo Zhu; Liang-liang Sun; Jian-xing Yang; Su-hang Chen; Feng-qi Zhao; Kang-zhen Xu (Energetic Materials Frontiers, 2025)
The pyrolysis behavior and mechanism of energetic materials are crucial for assessing their safety and application. In this study, the pyrolysis behavior, gas-phase decomposition products, condensate phase products and pyrolysis mechanism of high nitrogen compound 4,4′,6,6′-tetri(azide)-hydrazine-1,3,5-triazine (TAHT) were fully studied through differential scanning calorimetry (DSC), thermogravimetric analysis (TG), thermogravimetric-infrared-mass spectrometry (TG-IR-MS) and in-situ infrared spectroscopy. The results indicate that the thermal behavior of TAHT exhibits a big exothermic decomposition process and an endothermic decomposition process accompanied by the mass loss of 42.5 % and 52.1 %, respectively. At the heating rate of 10 °C·min−1, the peak temperature (Tp) and decomposition enthalpy of exothermic decomposition process are 230.4 °C and −2021.0 J g−1, respectively. The peak temperature (Tp) of endothermic decomposition process is 703.5 °C. In the exothermic decomposition stage, the main gas-phase decomposition products of TAHT are N2, and contain small amounts of NH3 and HCN, the hydrazine bond and azide groups in the condensed-phase almost completely disappear during the pyrolysis process, and the residues form a network structure of triazine ring. Based on the analysis of gas-phase and condensed-phase products, a possible pyrolysis mechanism for TAHT is proposed. This work provides valuable theoretical insights for the application of TAHT as a new green energetic material.